Effect of energy transfer modes on solidification cracking in pulsed laser welding. (October 2015) - Chelladurai, A. M.; Gopal, K. A.; Murugan, S.; Albert, S. K.; Venugopal, S.; Jayakumar, T.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, solidification cracking in pulsed laser welding of fully austenitic, AISI Type 316 stainless steel has been analysed at different energy transfer modes. The pulse parameters have been selected appropriately to obtain conduction, transition and keyhole mode welds. Conduction and transition mode welds exhibit higher susceptibility to cracking than keyhole mode welds. It is observed that both heat input and energy transfer mode affect the cooling rate and hence influence solidification cracking. Microstructures of the fusion zone have been analysed, and the cooling rate experienced by the weld is estimated from the mean cell size in the weld. It is found that the critical cooling rate below which cracking does not occur is ∼104 K s− 1.